IMPROVEMENT OF TECHNOLOGY OF REINFORCING STEEL PERIODIC PROFILE NUMBER 25, 28, 32 CLASS 500 - M. I. Titov; A. V. Rusalenko; V. V. Gordienko (Литьë и металлургия)
It is shown that the improvement of the technology of production of reinforcement № 25, 28, 32 Class 500 allowed to provide sufficient temperature of autotempered conducive to the emergence of a fixed yield plateau in the tension test diagram when determining the mechanical properties of reinforcing bars.